Medication rather than intoxication: acute occurrences by antihistamine in children - Costa, Gabriela Góes (2019)
OBJECTIVE: To analyze cases of cyproeptadine poisoning, from 2007 to 2015, in children between 1 to 12 years old, registered in the Centro de Informações Toxicológicas database in Belém, Pará State, Brazil. MATERIALS AND METHODS: Descriptive and retrospective study of poisoning cases in children from the Centro de Informações Toxicológicas of Belém. All poisonings caused by formulas containing vitamin-associated cyproheptadine from 2007 to 2015 were considered. The following variables were analyzed: gender, age, month, years, zone, time elapsed from exposure, signs, symptoms, and evolution of the cases. Epi InfoTM v6.6 and Microsoft Excel Starter 2010 were used for data analysis. RESULTS: Of the 1,719 cases of drug poisoning, 60 (3.5%) were caused by cyproheptadine in the study age group. The male gender was the most affected (75.0%) and the age group of 1 to 4 years old (80.0%). The cases occurred mostly in the urban area (96.7%), with the time between the accident and the attendance of 1 to 5 h (38.3%). The most frequent symptoms were agitation, drowsiness, and mental confusion. CONCLUSION: The circumstances of the cases were mainly due to accidental ingestion of more than the recommended amount, which mostly evolved to cure. These data serve to alert healthcare professionals about the use of appetite stimulants such as cyproheptadine.